The Motivations And Barriers Of Teachers’ Professional Development Activities During The Movement Control Order (MCO) – A Preliminary Insight - Ahmad Safian, Asraf Hadzwan; Robani, Anidah; Sedek, Muliati (IJLTER, 2021)
Due to the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) or COVID-19 pandemic, the education sector in Malaysia opted for the practice of online communication as a new norm. However, even during the pandemic, teachers in Malaysia are obliged to involve with professional development (henceforth, PD) activities for at least 42 hours annually. This article is prepared from a preliminary study to report the motivating factors and barriers on teachers’ PD activities during Malaysia’s Movement Control Order (henceforth, MCO). Also, this article studied the prevalence and trend of the teachers’ online communication during the period. A survey was conducted as a pilot study on 35 teachers from Sri Laksamana Primary School (henceforth, SLPS) in Melaka. The data gained were analysed descriptively using the SPSS software. In general, the results indicate that teachers are motivated to involve with online PD activities by getting rewarded with annual performance evaluation marks, which is beneficial for their career mileage. Next, the most significant barrier for their online PD is time limitation due to other workloads. In conclusion, even though the teachers are well accepting online PD activities, teachers should be given a higher portion of evaluation marks regarding their annual PD involvement than the current five per cent portion. Next, the school’s administrators should act on teachers’ work distribution issues that became the main challenge for effective online PD, thus creating a favourable working ecosystem.